Two distinct light-induced reactions are needed to promote germination in spores of Ceratopteris richardii - Cannon, Ashley E.; Sabharwal, Tanya; Salmi, Mari L.; Chittari, Ganesh Kumar; Annamalai, Valli; Leggett, Lindsey; Morris, Hope; Slife, Cameron; Clark, Greg; Roux, Stanley J. (Frontiers in Plant Science, 2023)
Germination of Ceratopteris richardii spores is initiated by light and terminates 3-4 days later with the emergence of a rhizoid. Early studies documented that the photoreceptor for initiating this response is phytochrome. However, completion of germination requires additional light input. If no further light stimulus is given after phytochrome photoactivation, the spores do not germinate. Here we show that a crucial second light reaction is required, and its function is to activate and sustain photosynthesis. Even in the presence of light, blocking photosynthesis with DCMU after phytochrome photoactivation blocks germination. In addition, RT-PCR showed that transcripts for different phytochromes are expressed in spores in darkness, and the photoactivation of these phytochromes results in the increased transcription of messages encoding chlorophyll a/b binding proteins. The lack of chlorophyll-binding protein transcripts in unirradiated spores and their slow accumulation makes it unlikely that photosynthesis is required for the initial light reaction. This conclusion is supported by the observation that the transient presence of DCMU, only during the initial light reaction, had no effect on germination. Additionally, the [ATP] in Ceratopteris richardii spores increased coincidentally with the length of light treatment during germination. Overall, these results support the conclusion that two distinct light reactions are required for the germination of Ceratopteris richardii spores.